Incertitude du résultat et demande du public : l`intensité compétitive intra-match comme variable clé - Scelles, N.; Durand, C. (Science et motricité, 2010)
In the literature, competitive balance (CB) concept is envisaged through three levels: on the end of a match before its kick-off, at the end of a season and on several seasons (Szymanski, 2003). The subject of this article is to propose a fourth dimension: intra-match CB. Besides the used approach incorporates fluctuations of the state of the score. This contribution completes CB by competitive intensity (CI) concept. Football Champions League 1955-2008 is the analysed case via a method which tackles all the played fixtures (3 889 matches). The results show a regular improvement of CI for each match taken individually. In contextualising (taking into account of placing and/or score of the first leg), progress is more marked.